2022
DOI: 10.1177/00031348221124331
|View full text |Cite
|
Sign up to set email alerts
|

Indications and Outcomes of Completion Cholecystectomy: A 5-year Experience From a Rural Tertiary Center

Abstract: Background Completion cholecystectomy (CC) is performed for recurrent or persistent biliary symptoms following subtotal cholecystectomy (STC) or incomplete cholecystectomy (IC). Due to its complexity, cases are often referred to hepato-pancreato-biliary (HBP) surgeons. There is little published literature on indications or outcomes of CC. Methods Completion cholecystectomy cases performed between 2016 and 2021 by the sole HPB surgeon covering a rural referral base of >250-mile radius in West Texas were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…2 Risk factors for post-cholecystectomy choledocholithiasis (PCC) are long cystic duct stump and SC or IC. [3][4][5] A study of 362 patients who had undergone a laparoscopic cholecystectomy (LC) for benign disease had a PCC incidence of 23.5%. The authors found a median cystic duct stump length on MRI of 31mm or greater was a significant risk factor for PCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Risk factors for post-cholecystectomy choledocholithiasis (PCC) are long cystic duct stump and SC or IC. [3][4][5] A study of 362 patients who had undergone a laparoscopic cholecystectomy (LC) for benign disease had a PCC incidence of 23.5%. The authors found a median cystic duct stump length on MRI of 31mm or greater was a significant risk factor for PCC.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 IC differs from SC in that it is due to improper identification of the anatomy intraoperatively resulting in ligation and division of the gallbladder body or fundus instead of the cystic duct, therefore leaving a reconstituted gallbladder remnant. 4 Currently, there is no consensus on the optimal method of SC and each subtype has its own pitfalls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These procedures were completed robotically without complication, and the patients had no further issues. 13 There is a possibility that among the 12.3% of patients in the group that were lost to followup, some may have been lost before the need for reintervention was recognized and may have sought care at other referral centers for this complication; this would result in under-estimation of the reoperation rate.…”
Section: Discussionmentioning
confidence: 99%
“…These procedures were performed by a hepatopancreaticobiliary surgeon at the same institution, and are described in detail elsewhere. 13…”
Section: Completion Cholecystectomymentioning
confidence: 99%